(untitled) (IIUC Business Review, 2021)
This study investigates the role of financial inclusion on bank stability in Bangladesh. Financial inclusion indicates equality and availability of financial products to individuals and businesses, which is captured with natural logarithm of number of ATM per 100 thousand of people (lnATM), log of number of bank branch (lnBB), ratio of Private Credit to Gross Domestic Product (PCGDP), ratio of financial system deposit to GDP (FSDGDP). Conversely, bank stability is proxied by natural logarithm of Z-score (lnZ-score), and ratio of non-performing loan to gross loan (NPL ratio). In the investigation process, we have used an unbalanced panel dataset consisting of all commercial banks from Bangladesh over the 2002-2014 period. Controlling a number of bank-level and macro-economic variables, the random effect model demonstrates that financial inclusion is positively related with bank solvency and negatively related credit risk taking. The results suggest that financial inclusion is supportive for promoting bank stability in Bangladesh. Therefore, the paper proposes to bolster financial innovation in order to increase financial in Bangladesh. IIUC Business Review Vol. 10, Dec. 2021 pp. 81-100